MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA CINANGNENG, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Ria Kusumaningrum; Susi Melinasari; Alda Herawati (SAHID DEVELOPMENT JOURNAL, 2022)
Micro, Small and Medium Enterprises (MSMEs) in the national economy have an important and strategic role. However, most MSMEs face capital constraints and limited access to formal financial institutions such as Islamic microfinance institutions. Baitul Maal Wat Tamwil (BMT) is a sharia microfinance institution that can be a solution to obstacles. This community service aims to program access to sharia financing for MSMEs. This community service is held from July to August 2021 and is located in Cingneng Village, Tenjolaya District, Bogor Regency. The community, especially MSMEs are actively involved in this community service, and this is a practice of the active participation method used in this community service. It is expected that BMT sharia financing has a positive and significant effect on changes in MSME profits.